Promising reduction of de novo resistance to endocrine therapies in breast cancer by small molecules from natural origin: a structural approach - Etti, Imaobong C.; Kadir, Arifah A.; Uweh, Esther J.; Okuku, Cecilia; Abdullah, Rasedee (University of Benin, 2024)
Purpose: To investigate the pharmacokinetic properties and inhibitory binding interaction between naturally occurring phytochemicals and a mutated human estrogen receptor (hERα) using an in silico approach. Methods: Naturally occurring small molecules, viz, myricetin, catechin, pinobanksin, pinocembrin, gelagin and pinostrobin, were investigated for their drug-likeness and pharmacokinetic properties. After that, molecular docking was used to study their binding affinities to Y537S (Tyr537Ser: a mutated estrogen receptor alpha, prominent in metastatic breast cancers). The structure of the ligand-binding domain (LBD) of human estrogen receptor was retrieved from Protein Data Bank while the structures of the studied compounds were collected from PubChem database. Using Schrodinger docking studio, the binding interactions of each phytochemical were investigated with the mutated estrogen receptor. Results: All studied compounds were observed to be drug-like with good physicochemical properties. Myricetin, catechin, pinobanksin, pinocembrin, gelagin and pinostrobin showed good solubilities in human oral absorption and good intestinal permeability, which are the rate-limiting barriers for oral drug absorption. The distribution of the studied ligands and their plasma protein binding parameters were better than those of tamoxifen, which has previously been reported with high potential binding to albumin. None of the studied compounds showed central nervous system toxicity. The binding studies revealed good inhibition of the LBD of Y537S-hERα. This is a targeted approach to selectively inhibit this receptor which has been reported to confer ligand-independent functions to ERα. This inhibition prevents downstream signaling and metastasis, rendering breast cancer cells harboring such mutations susceptible to apoptosis upon treatment with endocrine therapies. Conclusion: The compounds have the potential to mitigate de novo resistance in breast cancer cells harboring mutated estrogen receptors and should be further investigated as they are promising for oral delivery.